Bibliography on Cold Regions Science and Technology. Volume XXIV, Part 1. - COLD REGIONS RESEARCH AND ENGINEERING LAB HANOVER N H (1970)
The Bibliography on Cold Regions Science and Technology is a continuing publication of the Cold Regions Bibliography Section in the Science and Technology Division of the Library of Congress. It is sponsored by and prepared for the Cold Regions Research and Engineering Laboratory (formerly for the Snow, Ice and Permafrost Research Establishment) of the U.S. Army Corps of Engineers. With volume 20 the title was changed to Bibliography on Snow, Ice and Frozen Ground, with Abstracts, and with volume 23 the current title was adopted. The present volume contains material ac essioned between July 1969 and June 1970. The volume consists of two parts, each separately bound. Pt. 1 contains the full citation of 3628 items, numbered 24-1 through 24-3617, 24-4002, 24-4003, 24-4005 through 24-4008 and 24-4010 through 24-4014. (Author) See also Volume 23, AD-696 404, and Volume 24 Index, AD-715 717.